The history of Africa : the quest for eternal harmony - Asante, Molefi Kete, 1942- (2019)
Authoritative and comprehensive, The History of Africa provides an accessible narrative from earliest prehistory to the present day, with unusual attention paid to the ordinary lives of Africans. This survey includes a wealth of indigenous ideas, African concepts, and traditional outlooks that have escaped the writing of African history in the West. The fully updated new edition includes information on the recent conflicts in Libya and the Sudan, as well as additional content on the experiences and contributions of women. A companion website offers a wealth of supporting resources for each chapter, including new historic maps, primary sources, video and audio clips, and links to sites for further research. Richly illustrated and clearly written, this volume is an indispensable introduction to the major developments, personalities, and events that have shaped the history of the African continent.--Provided by publisher.
Africa and the origin of humanity -- Africa and the beginning of civilization -- The rise of Kemet -- The elements of early African civilization -- Governance and the political stability of Kemet -- The emergence of the great river kingdoms -- The spread of classical empires and kingdoms -- The Sudanic empires: historians and their narratives -- Generators of traditional and contemporary Africa -- Societies of secrets and institutions -- Arab and European missionaries, merchants, and mercenaries -- Resisting Arab and European slave traders -- Africa regains consciousness in a Pan African explosion -- Africa consolidates independence -- Toward a United States of Africa.
Includes bibliographical references and index.
Keywords: Africa -- History; Africa -- Civilization